Passive Planar Microwave Devices - Fernandez-Prieto, Armando; Martinez-Ros, Alejandro Javier (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of this book is to highlight some recent advances in microwave planar devices. The development of planar technologies still generates great interest because of their many applications in fields as diverse as wireless communications, medical instrumentation, remote sensing, etc. In this book, particular interest has been focused on an electronically controllable phase shifter, wireless sensing, a multiband textile antenna, a MIMO antenna in microstrip technology, a miniaturized spoof plasmonic antipodal Vivaldi antenna, a dual-band balanced bandpass filter, glide-symmetric structures, a transparent multiband antenna for vehicle communications, a multilayer bandpass filter with high selectivity, microwave planar cutoff probes, and a wideband transition from microstrip to ridge empty substrate integrated waveguide.